The role of VAP-1 in cardiovascular disease: a review - Chen, Chengqian; Zhong, Wentao; Zheng, Hao; Zhao, Wei; Wang, Yushi; Dong, Qi; Shen, Botao (Frontiers in Cardiovascular Medicine, 2025)
Cardiovascular diseases (CVD) remain the primary cause of morbidity and mortality in developed countries, highlighting the urgent need to identify biomarkers associated with CVD and its risk factors. Vascular adhesion protein-1 (VAP-1), a 170 kDa surface molecule expressed predominantly by endothelial cells, smooth muscle cells, and adipocytes, has garnered significant attention in this field. Beyond its role in inducing inflammatory mediators, VAP-1 is closely linked to coronary artery disease, heart failure, diabetes, obesity, and other CVDs, along with their associated risk factors. Notably, elevated plasma VAP-1 activity has been observed in patients with CVD and diabetes. The toxic metabolites produced by its enzymatic activity contribute to vascular endothelial injury and oxidative stress, thereby accelerating atherosclerosis and diabetes-related cardiovascular complications. Consequently, understanding the pathophysiological roles of VAP-1 in CVD has become a major research focus. This review examines the effects of VAP-1 on CVD pathogenesis and explores the therapeutic potential of VAP-1 inhibitors in managing these conditions.